The last woman of Warsaw : a novel - Batalion, Judith (Dutton, an imprint of Penguin Random House, 2026)
A debut novel by the critically acclaimed New York Times bestselling author of The Light of Days , following two very different Jewish women in Warsaw in the late 1930s as they unexpectedly come together in their search for love, meaning, and a sense of home, and as they grapple with the storm clouds gathering around them 1938: Fanny Zelshinsky is a sophisticated, modern daughter of the city's Jewish elite who wants nothing more than to be recognized as a legitimate artist by her family, her radical professor whom she idolizes, and the world at large. And all while she wonders if she is really going to go through with her wedding. Meanwhile, Zosia Dror has left behind her small northeastern shtetl and religious family in the wake of violence. Part of a budding youth movement that believes in social equality and creating a Jewish homeland, all she wants is to not get distracted by the glitz and hubbub of the city: or by the keen eyes of a certain tall, handsome comrade. When legendary artist Wanda Petrovsky: both a member of Zosia's movement leadership and Fanny's beloved photography professor: goes missing, the two young women are thrown together in the pursuit of the elusive firebrand. Is Wanda simply hiding, or is her disappearance connected to the rise in antisemitic laws and university practices? Fanny and Zosia may be the most unlikely of allies, but they must bridge their differences to help someone they both care for: and dodge the danger mounting around them in the process.